2008
DOI: 10.1158/1078-0432.ccr-07-1310
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of OGX-011, a 2′-Methoxyethyl Phosphorothioate Antisense to Clusterin, in Combination with Docetaxel in Patients with Advanced Cancer

Abstract: Purpose: Clusterin is a cytoprotective chaperone protein that promotes cell survival and confers broad-spectrum treatment resistance. OGX-011 is a 2 ¶-methoxyethyl^modified phosphorothioate antisense oligonucleotide that is complementary to clusterin mRNA, has a prolonged tissue half life, enhances drug efficacy in xenograft models, and reduces clusterin expression in humans with a biologically effective dose of 640 mg.The objective of this study was to determine a recommended phase II dose of OGX-011in combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(56 citation statements)
references
References 21 publications
3
53
0
Order By: Relevance
“…Consistent with these accumulated findings (43), inhibition of CLU with OGX-011 synergistically enhances conventional and molecular targeted therapies in prostate cancer preclinical models (25). Indeed, OGX-011 is now in phase III trials, as phase II studies reported more than 90% inhibition of CLU in human prostate cancer tissues (44) and 7 months prolonged survival when OGX-011 is combined with docetaxel in CRPC (45,46).…”
Section: Discussionmentioning
confidence: 77%
“…Consistent with these accumulated findings (43), inhibition of CLU with OGX-011 synergistically enhances conventional and molecular targeted therapies in prostate cancer preclinical models (25). Indeed, OGX-011 is now in phase III trials, as phase II studies reported more than 90% inhibition of CLU in human prostate cancer tissues (44) and 7 months prolonged survival when OGX-011 is combined with docetaxel in CRPC (45,46).…”
Section: Discussionmentioning
confidence: 77%
“…MicroRNA-based cancer gene therapy (reviewed by Tong andNemunaitis, 2008 andWeinberg, 2009a) offers the possibility of targeting multiple gene networks controlled by an individual miRNA (Valastyan and Weinberg, 2009b). The efficacy of localized small interfering RNA-based therapeutics (Devi, 2006;de Fougerolles et al, 2007;Davis et al, 2010) against various tumors is currently being assessed in a number of ongoing clinical trials (Tolcher et al, 2002;Chi et al, 2008;Hau et al, 2009). Similarly, miRNAs can be inhibited in vitro with specific cholesterol conjugated (Krutzfeldt et al, 2005), 2 0 -Omethyl oligonucleotide antagonists (AMOs) or 'antagomirs', when delivered as liposomal complexes, or nonconjugated (Esau et al, 2006) into mice, rats and nonhuman primates (Elmen et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among the stress signals that cause up-regulation of clusterin are chemotherapy, irradiation, and hormone ablation (28, 30, 31, 46 -49). A clusterin-inhibiting antisense oligonucleotide has been reported as a potential treatment for increasing the susceptibility of solid tumors to conventional cancer therapies (50,51). Here, we demonstrate that clusterin-I, designed as an antagonist of clusterin, has anticancer effect in vitro (Fig.…”
Section: Discussionmentioning
confidence: 53%